Discovering the effects of integrated green space air regulation on human health: A bibliometric and meta-analysis. (December 2021) - Qiu, Yue; Zuo, Shudi; Yu, Zhaowu; Zhan, Yu; Ren, Yin
Highlights: The first bibliometric and meta -analysis to explore the GS and air pollution. The impacts of air pollution on green space (GS) and ecosystem are always important. Studies about impacts of green spaces on human health rose in the past ten years. Exposure to greenness decreases risk of respiratory, LBW, and cardiovascular diseases. The larger buffer zone inclusion, the greater the impact of GS on the risks. Abstract: A considerable volume of literature investigating the associations between green space and air pollution was carried out in different disciplines. Although the air regulation effect of green space received much attention, the influence mechanism among green space, air quality and human health remains unclear, which needs a systematic and interdisciplinary review and summary. Therefore, on the basis of bibliometric and meta -analysis, we put forward the impact of air pollution on natural ecosystem and the potential impact pathway of green space on human health. Based on scientific publications from January 1990 to July 2021, the bibliometric analysis visualized the collaboration network of the authors, keywords, and institutions. The highly cited reference, knowledge clusters, keyword frequency identified the hot and challenging research prospects. The meta -analysis on 33 qualified studies was conducted on the association between green space, human health and air pollution. We found that, from the 2000s, the increase in the number of articles and journals about this topic sped up. The impacts of air pollution on green spaces and ecosystem always attract scholars' attentions. Furthermore, studies about impacts of green spaces on human health rose in the past ten years. However, the mechanism of green spaces on human health via air quality regulation remains unclear. We proposed three influence mechanisms. The meta -analysis result showed a statistically significant association between the residential greenness versus respiratory disease, low birth weight, cardiovascular disease, other three diseases, except for allergic disease. The larger buffer zone inclusion, the greater the impact of residential greenness on the risks of all five diseases. To link the green space with human health, appreciable efforts are needed in the experimental design, data acquisition, and analysis methods in the future. This article provides the overview, research challenges about green space and air pollution, and the clues to link the air regulation effect of green space to human health.